Electrocoagulation Technology Based on Aluminum–Zinc Electrodes as an Environmentally Friendly Method for the Removal of Cr3+ and Cd2+ from Batik Wastewater - Sani Sani; Sherina Tri Syopianti; Delia Shelamita Prasetya; Ika Nawang Puspitawati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Industrial batik wastewater often contains elevated concentrations of heavy metals, particularly Cr3+ and Cd2+, which pose serious risks to aquatic environments due to their toxicity, persistence, and non-biodegradable nature. Effective treatment technologies are therefore essential. Electrocoagulation represents a promising approach, as it is a redox-based process that employs the electrolytic dissolution of Al–Zn electrodes to generate in situ aluminum hydroxide coagulants. These coagulants effectively adsorb, destabilise, and precipitate dissolved heavy metal ions. This study evaluates the effects of applied voltage and electrolysis time on the performance of the electrocoagulation process for heavy metal removal from batik wastewater under batch conditions. Experiments were conducted at voltages ranging from 10 to 50 V, electrolysis times of 80–160 minutes, and an electrode spacing of 2 cm. Optimal performance was achieved at 50 V and 160 minutes, reducing Cr3+ concentrations from 3.78 mg/L to 0.031 mg/L, Cd2+ from 2.55 mg/L to 0.021 mg/L, and total suspended solids (TSS) from 203.77 mg/L to 39 mg/L. These findings demonstrate that electrocoagulation offers significant advantages, including in situ coagulant generation without external chemical addition, formation of stable flocs, and high efficiency in separating heavy metal contaminants. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production